2011
DOI: 10.1242/jcs.098855
|View full text |Cite
|
Sign up to set email alerts
|

VAB-10 spectraplakin acts in cell and nuclear migration in Caenorhabditis elegans

Abstract: Cytoskeletal regulation is important in cell migration. The Caenorhabditis elegans gonadal distal tip cells (DTCs) offer a simple model with which to investigate the mechanism of cell migration in organogenesis. Here, we report that one of the spectraplakin isoforms, VAB-10B1, plays an essential role in cell and nuclear migration of DTCs by regulating the actin and microtubule (MT) cytoskeleton. In the vab-10(tk27) mutant, which lacks VAB-10B1, alignment of filamentous (F)-actin and MTs was weakly and severely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Finally, not only BIN1 bridges CLIP-170 and nesprin, but it also interacts with actin -as nesprin does-suggesting that the tethering of the nucleus to both actin filaments and MTs by Amphyphisin-2/BIN1/ CeAMPH-1 is important for its proper positioning. This dual role of actin and MTs in nuclear positioning through a common cytolinker has also been observed during somatic gonad migration in C. elegans (Kim et al, 2011). The key role of the actin cytoskeleton is further evidenced by the identification of a SUN-KASHindependent pathway for nuclear migration (Chang et al, 2013), mediated by another conserved F-BARdomain containing protein called TOCA-1 (Transducer of CDC-42-dependent actin assembly).…”
Section: Mt-associated Proteinsmentioning
confidence: 68%
See 2 more Smart Citations
“…Finally, not only BIN1 bridges CLIP-170 and nesprin, but it also interacts with actin -as nesprin does-suggesting that the tethering of the nucleus to both actin filaments and MTs by Amphyphisin-2/BIN1/ CeAMPH-1 is important for its proper positioning. This dual role of actin and MTs in nuclear positioning through a common cytolinker has also been observed during somatic gonad migration in C. elegans (Kim et al, 2011). The key role of the actin cytoskeleton is further evidenced by the identification of a SUN-KASHindependent pathway for nuclear migration (Chang et al, 2013), mediated by another conserved F-BARdomain containing protein called TOCA-1 (Transducer of CDC-42-dependent actin assembly).…”
Section: Mt-associated Proteinsmentioning
confidence: 68%
“…This is the case for nuclear positioning and probably trafficking. The identification of the specific proteins, such as amphyphisin (D'Alessandro et al, 2015) and the spectraplakin VAB-10B (Kim et al, 2011) in nuclear positioning, or complexes, such as EXC-6 and possibly STRIPAK (Lant et al, 2015;Shaye and Greenwald, 2015) in trafficking, that bridge and coordinate both cytoskeletal networks, and of the signaling events taking place at such hubs will be important. In addition, a systematic investigation of the motor proteins acting in transport or positioning would be welcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, VAB-10B protects cells from internal shearing forces, as it likely anchors cortical actin to the MT network (Bosher et al, 2003). VAB-10B also directs nuclear translocation and cell migration in gonadal distal tip cell by mediating actin filament and MT crosslinking (Kim et al, 2011). Furthermore, a recent study demonstrated that VAB-10A can link the C. elegans fusogenic protein epithelial fusion failure 1 (EFF-1) to the F-actin network and so enhance cell-cell fusion (Yang et al, 2017).…”
Section: Spektraplakin Functions In Invertebrates Vab-10mentioning
confidence: 97%
“…20 Shot, the only member of the plakin family in the fly genome, was originally identified as a provider of mechanical linkage between the cortical actin and MTs. 21,22 Similarly in C. elegans, the intracellular role of spectraplakins in nuclear anchoring and movement 23 seems to be more ancient. Interestingly, in a recent S2-cell based screen, nesprins and Shot were also identified as factors involved in nuclear morphology, 24 possibly indicating a more general role in protecting nuclei.…”
Section: A Newly Discovered Ancient Role For Spectraplakin In Mechanimentioning
confidence: 99%